How do Emotional Values and Consumers’ Perceptions of Celebrity Endorsements Relate to Their Overall Satisfaction With a Cafe? - Joko Ramadhani; Muhammad Dharma Tuah Putra Nasution; Nurafrina Siregar (CV. Ulil Albab Corp, 2024)
This study aims to investigate the influence of consumers' perception of celebrity endorsement and their emotional values on customer satisfaction, both partially and simultaneously. Employing a quantitative associative research approach with a cross-sectional design, data were collected through purposive sampling from individuals who visited the Masbrow Café (N = 95). Written questionnaires were utilized as the primary data collection method, employing established instruments derived from prior research to measure customer satisfaction, emotional values, and perceptions of celebrity endorsement. Data analysis, conducted using advanced statistical methods such as regression analysis and ANOVA with SPSS version 25, revealed significant effects of emotional values and celebrity endorsement on customer satisfaction. Both emotional values and celebrity endorsement were found to significantly contribute to customer satisfaction. These findings underscore the importance of considering both emotional appeals and celebrity endorsements in marketing strategies aimed at enhancing customer satisfaction. Implications and limitations of the study are discussed to provide insights for future research and practical applications.